Plantago major leaf extract against bacteria and fungi of medical importance - de Sousa, Débora Silva Marques [UNESP]; Ruiz, Luciana da Silva; Pereira, Ana Flávia Marques [UNESP]; Sani, Alessandra Aguirra [UNESP]; Zapata, Tatiane Baptista [UNESP]; Monari, Gabrielle Pires de Morais; da Rosa, Cassiana Ferreira; Fernandes Junior, Ary [UNESP]; Rall, Vera Lucia Mores [UNESP]; Prado, Diego Godina; de Oliveira, Alberto; Bosco, Sandra de Moraes Gimenes (FapUNIFESP (SciELO), 2025)
Antimicrobial drug resistance is a challenge to public health. Various microorganisms, including methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa, carbapenemase-producing Klebsiella pneumoniae, Pythium insidiosum, and Candida auris, have developed resistance to commonly used antimicrobials in infection disease treatments. Consequently, there is an urgent need to explore and develop novel therapeutic drugs. Natural products, particularly medicinal plants, have received attention in the quest for innovative treatments for various diseases. Plantago major is a plant endowed with several biological properties, such as antibacterial, antifungal, and healing actions. This study aimed to investigate the antimicrobial activities of the methanolic extract obtained from the leaves of P. major. Microdilution assays were conducted to determine the minimum inhibitory concentration and minimum bactericidal and fungicidal concentration. Additionally, synergism with antimicrobial drugs was assessed using a time-kill curve analysis. A synergistic bactericidal interaction between the extract and imipenem was observed against carbapenemase-producing K. pneumoniae. For MRSA, a bacteriostatic synergism was noted in combinations of the extract with cephalotin and oxacillin. For C. auris, a fungistatic interaction was observed between the extract and amphotericin B. These results suggest the presence of bioactive compounds within the extract with therapeutic potential for combating infections caused by these microorganisms.
Keywords: Antimicrobial drugs; Extract chemical composition; Mass spectrometry; Multi-drug resistant microorganisms; Natural products; Synergistic interaction